The Other Side of Through: Young Breast Cancer Survivors' Spectrum of Sexual and Reproductive Health Needs. (November 2020) - Black, Kristin Z.; Eng, Eugenia; Schaal, Jennifer C.; Johnson, La-Shell; Nichols, Hazel B.; Ellis, Katrina R.; Rowley, Diane L.
The long-term reproductive health impact of cancer treatments is a concern for premenopausal women with a history of breast cancer. This study examined the unmet sexual and reproductive health needs of breast cancer survivors, as well as concordances and discordances in needs by childbearing status and race. We interviewed 17 women diagnosed with breast cancer between the ages of 18 and 45 years and living in North Carolina. To analyze these data, we used the Sort and Sift, Think and Shift© method, a multidimensional qualitative analysis approach. We learned that breast cancer survivors (a) received limited reproductive health information, (b) desired realistic expectations of conceiving postcancer, (c) struggled with adjusting to their altered physical appearance, and (d) had menopause symptoms that led to sexual health and quality of life issues. Breast cancer survivors are in need of and desire more education and resources to address their sexual and reproductive health concerns.